PENDIDIKAN KONSERVASI MANGROVE PADA SISWA SEKOLAH DASAR SEKOTONG TENGAH - Kornelia Webliana B (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract: Conservation education is an essential process that should be trained to young generation from an early age to create a young generation who loves nature and is environmentally friendly. Mangrove Ecosystem is one of the conservation education learning facilities that need to be established in coastal areas. This extension activity aims to (1) design models and learning methods for conservation education for elementary school students in the Central Sekotong area(2) develop a guide to introducing mangrove ecosystems as a learning medium for conservation education. The extension program took place in Sekotong Village, West Lombok, and focuses on joint activities with the Central Sekotong Village Government, Central Sekotong State Elementary School No 1, and the manager of the Tanjung Batu Mangrove area, Central Sekotong Village. The location was selected using the purposive sampling method. The method of extension activities includes Focus group discussion (FGD), dialogues, and socialization. The results of the extension program show that the village government, educators of the Central Sekotong State Elementary School No 1, and the manager of the Tanjung Batu Mangrove area support the application of the outdoor study method to elementary school students. The learning method is expected to increase students' knowledge regarding environmental issues. Students could also understand the importance of maintaining the ecological function of coastal and marine biodiversity in the Central Sekotong region. Compilation of a learning guidebook done, by the extension team, to support the application of the learning model. It contains information on the mangrove ecosystem for elementary school students, entitled 'Guidance for Introduction to Mangroves for Elementary School Students. Keywords : Education, Conservation, Mangrove, Tanjung BatuAbstrak: Pendidikan konservasi merupakan salah satu proses penting yang harus ditanamkan sejak dini untuk menciptakan generasi muda yang cinta alam dan berwawasan lingkungan. Salah satu media pembelajaran pendidikan konservasi yang dapat dikembangkan di kawasan pesisir adalah Ekosistem Mangrove. Pengabdian ini bertujuan untuk (1)mendesain model dan metode pembelajaran pendidikan konservasi bagi siswa sekolah dasar di kawasan Sekotong Tengah (2)menyusun panduan pengenalan ekosistem mangrove sebagai media pembelajaran pendidikan konservasi. Pengabdian dilaksanakan di Desa Sekotong, Lombok Barat, dengan fokus kegiatan bersama Pemerintah Desa Sekotong Tengah, Sekolah Dasar Negeri 1 Sekotong Tengah, dan pengelola kawasan Mangrove Tanjung Batu, Desa Sekotong Tengah. Metode pemilihan lokasi menggunkan purposive sampling, dan metode kegiatan pengabdian yaitu Focus group discusion (FGD), diskusi dan sosialisasi. Hasil pengabdian menunjukan pemerintah desa, para guru Sekolah Dasar Negeri 1 Sekotong Tengah, dan pengelola kawasan Mangrove Tanjung Batu mendukung penerapan metode oudoor study pada siswa Sekolah Dasar. Metode pembelajaran ini diharapkan dapat meningkatkan pengetahuan siswa terkait persoalan lingkungan, serta memahami pentingnya menjaga eksistensi fungsi ekologi dari keanekaragaman hayati wilayah pesisir dan laut di wilayah Sekotong Tengah. Dalam rangka mendukung penerapan model pembelajaran telah tersusun buku panduan pembelajaran yang berisikan informasi dasar ekosistem mangrove bagi siswa sekolah dasar yang diberi judul ‘Panduan Pengenalan Mangrove pada Siswa Sekolah Dasar’. Kata Kunci : Pendidikan, Konservasi, Mangrove, Tanjung Batu